Guardians of the galaxy - Gunn, James, 1970-; Perlman, Nicole; Feige, Kevin; Pratt, Chris, 1979-; d ctor.; Batista, Dave, 1969-; Diesel, Vin; Cooper, Bradley; Pace, Lee, 1979-; Rooker, Michael, 1955-; Gillan, Karen, 1987-; Hounsou, Djimon, 1964-; et al. (Burbank, California : Buena Vista Home Entertainment, 2014)
Adventurer Peter Quill finds himself the object of a bounty hunt after stealing an orb coveted by Ronan. To evade Ronan, Quill is forced into an uneasy truce with a quartet of disparate misfits to bring balance to the glaxay.
Music, Tyler Bates; costume designer, Alexandra Byrne ; editors, Fred Raskin, Craig Wood, Hughes Winborne ; production design, Charles Wood ; director of photography, Ben Davis.
Chris Pratt, Zoe Saldana, Dave Bautista, Vin Diesel, Bradley Cooper, Lee Pace, Michael Rooker, Karen Gillan, Djimon Hounsou, John C. Reilly, Glenn Close, Benicio Del Toro.
MPAA rating: PG-13; for intense sequences of sci-fi violence and action, and for some language.
DVD, region 1, widescreen; 5.1 Dolby Digital.
English, French or Spanish dialogue; Spanish, English or French subtitles; subtitled for the deaf and hard of hearing; English descriptive audio.
Keywords: Bounty hunters -- Drama; Heroes -- Drama; Orbs -- Drama; Theft -- Drama; Superhero films; Outer space -- Drama; Action and adventure films; Feature films; Fiction films; Video recordings for the hearing impaired